Stanowisko ks. Josyfa Łewyćkiego (1801-1860) w sporze o alfabet języka ruskiego (ukraińskiego) w Galicji w latach 30. i 40. XIX wieku - Dwornik, Kamil (Acta Polono-Ruthenica, 2018)
In the 30s of 19th century the Ruthenian (Ukrainian) national movement in the Austrian Galicia was dominated by the dilemma of so called azbuchna vijna (Ukrainian „alphabet war”). The dispute among the national activists was about the change the Cyrillic script to the Latin alphabet adopted from Polish language. This paper presents the arguments of Greek-Catholic father Josyph Levytskyi, who was the most influential critic of the idea of latinization. He published his ideas in a small booklet that was distributed together with the Polish weekly „Rozmaitości” . Levytskyi stressed on long history of the Cyrillic alphabet and its uniqueness. Moreover, he claimed that new alphabet will not make Ruthenian literature more European and will only give the Poles another reason to call Ruthenian language a variety of Polish. On the other hand, Levytskyi did not appraised very much the usage of grazhdanka by the „Rus Trinity” and criticised the new orthography, which was based on phonetic principle. Key words: Latin, Cyrillic, Ukrainian, alphabet war, Levytskyi.